2015
DOI: 10.1089/neu.2014.3508
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Degradation Inhibition Improves Neurobehavioral Function, Blood–Brain Barrier Integrity, and Neuroinflammation following Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is an increasingly frequent and poorly understood condition lacking effective therapeutic strategies. Inflammation and oxidative stress (OS) are critical components of injury, and targeted interventions to reduce their contribution to injury should improve neurobehavioral recovery and outcomes. Recent evidence reveals potential protective, yet short-lived, effects of the endocannabinoids (ECs), 2-arachidonoyl glycerol (2-AG) and N-arachidonoylethanolamine (AEA), on neuroinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 65 publications
5
93
1
Order By: Relevance
“…Very recently, enhancement of 2-AG signaling by inhibition of its major hydrolytic enzyme MAGL is also shown to attenuate neuroinflammation and neurodegeneration in the mouse model of mild traumatic brain injury (Katz et al, 2015;Zhang et al, 2015). In our previous studies, we have shown that a selective ABHD6 inhibitor WWL70 at 10 mg/kg has a better effect in blocking TBI-induced deficits in fine motor movement and motor coordination than WWL70 at 5 mg/kg (Tchantchou and Zhang, 2013).…”
Section: Inhibition Of Abhd6 Ameliorated Clinical Signs Of Eaementioning
confidence: 98%
“…Very recently, enhancement of 2-AG signaling by inhibition of its major hydrolytic enzyme MAGL is also shown to attenuate neuroinflammation and neurodegeneration in the mouse model of mild traumatic brain injury (Katz et al, 2015;Zhang et al, 2015). In our previous studies, we have shown that a selective ABHD6 inhibitor WWL70 at 10 mg/kg has a better effect in blocking TBI-induced deficits in fine motor movement and motor coordination than WWL70 at 5 mg/kg (Tchantchou and Zhang, 2013).…”
Section: Inhibition Of Abhd6 Ameliorated Clinical Signs Of Eaementioning
confidence: 98%
“…Because post-TBI alcohol exposure is detrimental to overall recovery through sustained neuroinflammation and excitatory glutamate signaling (Mayeux, Teng, Katz, Gilpin, & Molina, 2015), Dr. Molina’s overall aim is to understand the underlying mechanisms leading to escalation in alcohol drinking post TBI. It has been previously shown that modulation of endocannabinoid tone by systemic administration of JZL184, a monoacylglycerol lipase inhibitor that prevents degradation of the endocannabinoid 2-Arachidonoylglycerol (2-AG), is sufficient to attenuate neuroinflammation and improve neurobehavioral recovery (Katz et al, 2015). Therefore, Dr. Molina’s group tested the hypothesis that post-TBI endocannabinoid degradation inhibition would improve neurobehavioral outcomes, including escalation of alcohol drinking.…”
Section: Alcohol and Trauma/tissue Injurymentioning
confidence: 99%
“…A dye tracer extravasation method was applied for the detection of BBB integrity (20). Evans blue (2%, 2 ml/kg, intravenously) was administered 30 min prior to euthanasia.…”
Section: Macroscopic Evaluation Of Colitis Injurymentioning
confidence: 99%
“…Activation of the ECS decreased pro-inflammatory cytokine levels in mouse models of inflammation and sepsis (15,16), and also ameliorated neural inflammation and attenuated behavioral alterations in mice with Huntington's disease (17). Furthermore, elevation of endogenous arachidonoylethanolamide (AEA, also known as anandamide) levels via the inhibition of FAAH protected rats against aging-associated inflammatory responses in the hippocampus (18), attenuated Toll-like receptor 3-induced neural inflammatory responses (19), and ameliorated posttraumatic brain injury in mice (20). This evidence strongly suggests a neural protective role of the ECS.…”
Section: Introductionmentioning
confidence: 99%